Serum Level of 4-Hydroxynonenal in Community-Acquired Pneumonia: A Potential Biomarker for Severity and Prognosis - Jiang, Ya-Lin; Liu, Hong-Yan; Tang, Min-Min; Cheng, Jia-Yi; Zhao, Hui; Fu, Lin (Frontiers in Medicine, 2022)
Background Four-hydroxynonenal (4-HNE) exerts a central role in the pathophysiological process of pulmonary diseases. The aim of this project was to evaluate the correlations between serum 4-HNE with severity and prognosis in patients with community-acquired pneumonia (CAP) by a prospective cohort study. Materials and Methods A total of 239 patients with CAP and healthy volunteers were recruited. Fasting blood was collected. Serum 4-HNE was measured with ELISA. Clinical characteristics and demographic information were obtained. The relationships between serum 4-HNE and clinical characteristics were evaluated through the Spearman or Pearson correlation coefficient. The associations of serum 4-HNE with severity and prognosis were estimated through logistic regression analysis. Results On admission, serum 4-HNE was upregulated in patients with CAP compared with healthy volunteers. Serum 4-HNE was gradually increased in line with CAP scores. Additionally, elderly patients with CAP were more prone to suffer from 4-HNE elevation. Moreover, serum 4-HNE was positively correlated with CAP severity scores. Meanwhile, the poor prognostic outcomes were tracked among patients with CAP. Higher serum 4-HNE on admission increased the risks of mechanical ventilation, vasoactive agent usage, and death in patients with CAP during hospitalization. The predictive powers for severity and death were increased in serum 4-HNE compared with CAP severity scores and inflammatory cytokines. Conclusion Serum 4-HNE on admission is positively correlated with the severity and poor prognosis among patients with CAP, indicating that 4-HNE participates in the pathophysiology of CAP. Serum 4-HNE may be used as an earlier biomarker for diagnosis and prognosis in patients with CAP.